2014
DOI: 10.1167/iovs.14-15573
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled Study on the Effects of Lutein and Zeaxanthin on Photostress Recovery, Glare Disability, and Chromatic Contrast

Abstract: Citation: Hammond BR, Fletcher LM, Roos F, Wittwer J, Schalch W. A double-blind, placebo-controlled study on the effects of lutein and zeaxanthin on photostress recovery, glare disability, and chromatic contrast. Invest Ophthalmol Vis Sci. PURPOSE.Past studies have shown that higher macular pigment optical density (MPOD) and lutein (L) and zeaxanthin (Z) supplementation are related to improvements in glare disability, photostress recovery, and chromatic contrast. This study assessed those links using a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 33 publications
4
89
1
1
Order By: Relevance
“…46 Furthermore, it has been shown that lutein leads to improved CS, however, without increase in visual acuity, and thus may improve patients' quality of life. 5,47 As such, lutein supplementation may still be beneficial for a subgroup of patients suffering from ARM.…”
Section: Discussionmentioning
confidence: 99%
“…46 Furthermore, it has been shown that lutein leads to improved CS, however, without increase in visual acuity, and thus may improve patients' quality of life. 5,47 As such, lutein supplementation may still be beneficial for a subgroup of patients suffering from ARM.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Given the importance of MP for vision and its role in reducing risk of age-related macular degeneration (AMD) progression, 16 there is clearly a need to measure this pigment accurately in vivo in the clinical and the research setting. Moreover, it is important to be able to measure changes in MP over time.…”
Section: Acular Pigment (Mp) Is Composed Of the Carotenoids Lutein mentioning
confidence: 99%
“…Given the importance of MP for visual function in diseased [16][17][18] and nondiseased retinas, 19,20 and the emerging evidence that MP may be a useful biomarker for AD, 21,22 researchers and clinicians must measure MP levels accurately across different populations. A variety of techniques are available for measuring MP (and its constituent carotenoids) and the measurement techniques can be classified broadly as ex vivo (i.e., outside cell/tissue) and in vivo techniques (i.e., inside cell/tissue).…”
mentioning
confidence: 99%